2005
DOI: 10.1124/jpet.105.095331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Channel Blockade on Angiotensin II-Induced Peritubular Ischemia in Rats

Abstract: Recent studies have indicated that derangement of peritubular capillary (PTC) circulation with consequent tubulointerstitial hypoxia plays a pivotal role in the pathogenesis of renal injury. The present study was performed to determine whether azelnidipine, a new dihydropyridine calcium channel blocker, attenuates angiotensin II (AngII)-induced peritubular ischemia in anesthetized rats. The superficial PTCs were visualized directly using an intravital fluorescence videomicroscope system, and the PTC blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Recent studies have indicated that derangement of peritubular capillary circulation with consequent tubulointerstitial hypoxia plays a pivotal role in the pathogenesis of renal injury (37). It has been reported that AZ attenuates Ang II-induced peritubular ischemia, mitochondrial injury and apoptosis in hypoxic renal tubular cells (37,38). In the study of Nakamura et al (7), however, only a few subjects were treated with RAS inhibitors.…”
Section: Fig 2 the Correlation Between The % Change Of Blood Pressumentioning
confidence: 76%
“…Recent studies have indicated that derangement of peritubular capillary circulation with consequent tubulointerstitial hypoxia plays a pivotal role in the pathogenesis of renal injury (37). It has been reported that AZ attenuates Ang II-induced peritubular ischemia, mitochondrial injury and apoptosis in hypoxic renal tubular cells (37,38). In the study of Nakamura et al (7), however, only a few subjects were treated with RAS inhibitors.…”
Section: Fig 2 the Correlation Between The % Change Of Blood Pressumentioning
confidence: 76%
“…Azelnidipine attenuates angiotensin IIinduced peritubular ischemia and has antioxidative properties that may be involved in its beneficial effect on renal injury. 14 Although it has been reported that azelnidipine decreases not only urinary albumin excretion but also urinary 8-OHdG and L-FABP levels in diabetic nephropathy, 15,16 the dosage and kinds of RAS inhibitors were not fixed and the relationship between the changes in those urinary markers and the changes in plasma aldosterone levels are not well known. Therefore, the objective of this study was to determine the effects of additional therapy from the CCBs azelnidipine or amlodipine using the maximum recommended dose of ARB, 40 mg olmesartan, on BP control and renoprotection in hypertensive diabetic patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…2). Nishiyama's group recently provided direct evidence of the angiotensin II-induced reduction in blood flow by visualizing the superficial peritubular capillaries directly through an intravital fluorescence videomicroscope system (45). Evaluation of peritubular capillary blood flow by analyzing the velocity of fluoresceinlabeled erythrocytes showed a marked decrease in peritubular capillary blood flow in rats following the intravenous administration of angiotensin II.…”
Section: Angiotensin Ii-induced Functional Changes In Renal Circulationmentioning
confidence: 99%